An innovative and inexpensive experimental setup for testing connections in gridshell structures. (15th March 2020) - Seifi, Hamed; Rezaee Javan, Anooshe; Lin, Xiaoshan; Xie, Yi Min
Highlights: Experimentally studied the structural response of additively manufactured nodes. Proposed an innovative and inexpensive experimental setup for nodes in gridshells. The numerical modelling of the nodes validated the effectiveness of the test setup. Abstract: The design and manufacture of structural nodes for gridshell structures are complicated due to complex geometries and loading conditions. The validation of the design concepts of these nodes is even more challenging, because complex design loads are difficult to be applied in a laboratory test. In this paper, a testing rig is proposed and manufactured to test two different additively manufactured nodes. The two nodes are symmetrical and each connecting three members. These nodes are designed to sustain pure axial loads and pure out-of-plane bending moments, respectively. The results of the experiments show the importance of the bolt tolerance in the design of such a testing setup. Subsequently an innovative and inexpensive experimental setup is developed for testing nodes under dominant design loading conditions in gridshell structures. The proposed testing method is generalized, which can be applied to both individual and combined loading conditions, and the new testing rig can be easily fabricated at a low cost.